On Unitary Invariant Strongly Pseudoconvex Complex Landsberg Metrics (Journal of Mathematical Study, 2018)
In this paper,we prove that a unitary invariant strongly pseudoconvex complexFinsler metric is a complex Landsberg metric if and if only if it comes from aunitary invariant Hermitian metric. This implies that there does not exist unitary invariantcomplex Landsberg metric unless it comes from a unitary invariant Hermitianmetric.
Keywords: Unitary invariant; complex Landsberg metric; complex Finsler metric.